Whither activation policies? Reflections for the future - John P. Martin (Institute for the Study of Labor (IZA), 2016)
Activation policies aimed at getting working-age people off benefits and into work have been embraced by many OECD countries. In a previous paper, I have argued that activation strategies have performed well during the Great Recession and subsequent recovery in some, but not all, of these countries. At the same time it is pertinent to look to the future and to consider what challenges what challenges the activation paradigm is likely to face over the coming decades when US and European labour markets have to cope with ageing workforces and immigration, to name but two. In this paper, I set out my views on some of the major challenges facing activation strategies in the future.
Keywords: J01; J08; J68; 330; activation; active labour market policies; unemployment benefits; benefit conditionality; career progression